Unlocking the full potential of Earth observation during the 2015 Texas flood disaster. Issue 5 (7th May 2016) - Schumann, G. J‐P.; Frye, S.; Wells, G.; Adler, R.; Brakenridge, R.; Bolten, J.; Murray, J.; Slayback, D.; Policelli, F.; Kirschbaum, D.; Wu, H.; Cappelaere, P.; et al.
Abstract: Intense rainfall during late April and early May 2015 in Texas and Oklahoma led to widespread and sustained flooding in several river basins. Texas state agencies relevant to emergency response were activated when severe weather then ensued for 6 weeks from 8 May until 19 June following Tropical Storm Bill. An international team of scientists and flood response experts assembled and collaborated with decision‐making authorities for user‐driven high‐resolution satellite acquisitions over the most critical areas; while experimental automated flood mapping techniques provided daily ongoing monitoring. This allowed mapping of flood inundation from an unprecedented number of spaceborne and airborne images. In fact, a total of 27, 174 images have been ingested to the USGS Hazards Data Distribution System (HDDS) Explorer, except for the SAR images used. Based on the Texas flood use case, we describe the success of this effort as well as the limitations in fulfilling the needs of the decision‐makers, and reflect upon these. In order to unlock the full potential for Earth observation data in flood disaster response, we suggest in a call for action (i) stronger collaboration from the onset between agencies, product developers, and decision‐makers; (ii) quantification of uncertainties when combining data from different sources in order to augment information content; (iii) include a default role for the end‐user in satellite acquisition planning; and (iv) proactive assimilation of methodologies and tools into the mandated agencies.